Preparation method and application of bismuth oxychloride / TCN composite material with hierarchical structure
Through the hierarchical structure bismuth oxychloride/TCN composite material degraded antibiotics under light conditions and reduced CO2, the problems of poor antibiotic wastewater treatment and high energy consumption in the prior art are solved, and efficient catalytic and energy conversion are achieved.
Patent Information
- Application Number
- CN202411967741.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art has problems of poor catalytic effect, high cost and short service life when treating antibiotic wastewater. At the same time, traditional CO2 conversion technology consumes high energy and is harsh in conditions.
The graded structure bismuth oxychloride/TCN composite material is used to degrade antibiotics into non-toxic small molecules by using bismuth oxychloride under light conditions, and CO2 is reduced to chemical fuel by carbon nitride.
It is achieved by simultaneously removing antibiotics in a reaction system and producing high value-added chemical fuel, and the composite material has excellent catalytic properties and stability.
Smart Images

Figure CN119746912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and particularly relates to a preparation method and application of a hierarchical structure bismuth oxychloride / TCN composite material. Background Art
[0002] CO2 molecules are thermodynamically stable and kinetically inert. Their activation and chemical conversion usually require high energy input, such as high temperature and pressure, highly active catalysts or reaction substrates. Traditional CO2 conversion technology mainly uses thermal catalytic reduction of CO2 to produce various energy products or chemicals. However, these thermal reactions have the disadvantages of harsh reaction conditions, high energy consumption and high requirements for reaction equipment.
[0003] Wastewater containing antibiotics poses a serious threat to human health and the ecosystem. With the increasing number of antibiotics, the traditional activated sludge method of treating wastewater faces the problem of increasingly complex wastewater composition and poor treatment effect. At the same time, resistance genes may be generated during the wastewater treatment process, which makes biological treatment face great difficulties. In addition, the adsorption method only transfers antibiotics to a new phase, but does not completely eliminate them, which is easy to cause secondary pollution, and is also costly and has a short service life.
[0004] Therefore, there is an urgent need to provide a new catalyst for processing antibiotics, which has a good catalytic effect. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. The present invention provides a preparation method and application of a hierarchical bismuth oxychloride / TCN composite material. The hierarchical bismuth oxychloride / TCN composite material prepared by the preparation method of the present invention, wherein bismuth oxychloride and carbon nitride (TCN) serve as antibiotic degradation and CO2 reduction active centers respectively, and under light conditions, bismuth oxychloride can degrade antibiotics into non-toxic small molecules (such as CO2, H2O, etc.), and carbon nitride reduces CO2 into chemical fuels (such as CH4, CH3OH, etc.). The goal of simultaneously removing antibiotics in a reaction system and obtaining chemicals with high added value is achieved, and the bismuth oxychloride / carbon nitride composite material has excellent catalytic performance and catalytic stability.
[0006] In order to solve the above problems, the present invention provides the following technical solutions:
[0007] A first aspect of the present invention provides a method for preparing a hierarchical structured bismuth oxychloride / TCN composite material.
[0008] A method for preparing a hierarchical structure bismuth oxychloride / TCN composite material comprises the following steps:
[0009] (1) mixing melamine with phosphoric acid and water, heating, and then further heating, reacting, washing the reaction product to obtain a precursor, and calcining under a protective gas atmosphere to obtain tubular carbon nitride;
[0010] (2) soaking the tubular carbon nitride obtained in step (1) in an alkali solution, performing a surface hydrophilic treatment, and then washing to obtain the hydrophilic treated tubular carbon nitride, and then mixing the hydrophilic treated tubular carbon nitride, bismuth nitrate or bismuth nitrate hydrate, and ethylene glycol to obtain a solution A; dissolving 1-hexadecyl-3-methylimidazolium chloride (i.e., [C16-MIm]Cl) in ethanol to obtain a solution B, dropping the solution B into the solution, stirring, heating the obtained mixture for reaction, and finally collecting the obtained precipitate by centrifugation, washing, and drying to obtain the hierarchical structure bismuth oxychloride / TCN composite material.
[0011] Preferably, in step (1), the mass volume ratio of melamine, phosphoric acid and water is 1 g: (0.5-2.0) g: (80-100) mL, more preferably 1 g: 1.2 g: 80 mL.
[0012] Preferably, in step (1), the water is deionized water.
[0013] Preferably, in step (1), the heating temperature is 75-85° C., and the heating time is 0.5-1.5 hours. More preferably, the heating temperature is 80° C., and the heating time is 1 hour.
[0014] Preferably, in step (1), the reaction temperature is 170-180° C., and the reaction time is 8-10 hours. More preferably, the reaction temperature is 180° C., and the reaction time is 10 hours.
[0015] Preferably, in step (1), the reaction is carried out in a stainless steel high-pressure reactor.
[0016] Preferably, in step (1), the reaction product is fully rinsed with deionized water until the phosphorus species are removed.
[0017] Preferably, in step (1), the protective gas is nitrogen or a rare gas.
[0018] Preferably, in step (1), the calcination temperature is 500-550°C, and the calcination time is 3-4 hours. More preferably, the calcination temperature is 550°C, and the calcination time is 4 hours.
[0019] Preferably, in step (2), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution. The concentration of the alkali solution is 1-2M. M represents mol / L.
[0020] Preferably, in step (2), the washing is to wash the tubular carbon nitride with deionized water until it becomes neutral.
[0021] Preferably, in step (2), the usage ratio of the hydrophilically treated tubular carbon nitride, bismuth nitrate or bismuth nitrate hydrate, and ethylene glycol is 50 mg: (0.1-0.25) mmol: (5-10) mL, and more preferably 50 mg: 0.25 mmol: 5 mL.
[0022] Preferably, in step (2), the ratio of 1-hexadecyl-3-methylimidazolium chloride to ethanol is (0.01-0.05) mmol:(20-30) mL, more preferably 0.05 mmol:30 mL.
[0023] Preferably, in step (2), the heating reaction temperature is 150-160° C., and the heating reaction time is 8-10 hours. More preferably, the heating reaction temperature is 160° C., and the heating reaction time is 10 hours.
[0024] The heating reaction is carried out in a stainless steel high-pressure reactor.
[0025] Preferably, in step (2), the washing is performed with ethanol and deionized water.
[0026] Preferably, in step (2), the drying is performed at 40-60° C. overnight.
[0027] The second aspect of the present invention provides a hierarchical structure bismuth oxychloride / TCN composite material.
[0028] A hierarchical structure bismuth oxychloride / TCN composite material is prepared by the above preparation method.
[0029] The third aspect of the present invention provides an application of a hierarchical structured bismuth oxychloride / TCN composite material.
[0030] Application of a hierarchical bismuth oxychloride / TCN composite material in catalyzing the decomposition of antibiotics.
[0031] Preferably, the antibiotic comprises tetracycline.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The hierarchical structure bismuth oxychloride / TCN composite material prepared by the preparation method of the present invention, wherein bismuth oxychloride and carbon nitride (TCN) serve as antibiotic degradation and CO2 reduction active centers respectively, and under light conditions, bismuth oxychloride can degrade antibiotics into non-toxic small molecules (such as CO2, H2O, etc.), and carbon nitride reduces CO2 into chemical fuels (such as CH4, CH3OH, etc.). The goal of removing antibiotics in a reaction system and obtaining chemicals with high added value is achieved, and the bismuth oxychloride / carbon nitride composite material has excellent catalytic performance and catalytic stability.
[0034] (2) The hierarchical bismuth oxychloride / TCN composite material prepared by the preparation method of the present invention is a photocatalyst that has both the strong oxidizing ability of bismuth oxychloride and the strong reducing ability of carbon nitride (TCN). The hollow structure of the hierarchical bismuth oxychloride / TCN composite material enables multiple and multi-level scattering of incident light, significantly enhancing the material's ability to capture and absorb light. In addition, an effective heterojunction is formed between the two components, and the two synergistically improve the separation efficiency of photogenerated carriers. The hierarchical structure has a larger specific surface area, which is conducive to the adsorption of reactants and the transmission of reactants and products, so that CO2 reduction and antibiotic degradation reactions can be carried out on the surfaces of carbon nitride and bismuth oxychloride, respectively. This helps to achieve spatial separation of different reaction processes, thereby simultaneously obtaining renewable energy and antibiotic removal in one redox cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 X-ray diffraction spectra of BiOCl, TCN and 20% BiOCl / TCN samples;
[0036] Figure 2 IR spectra of BiOCl, TCN and 20% BiOCl / TCN samples;
[0037] Figure 3 The SEM image and element distribution of 20% BiOCl / TCN sample;
[0038] Figure 4 The photocatalytic tetracycline degradation performance diagram of different samples;
[0039] Figure 5 The photocatalytic CO2 reduction performance diagram of different samples;
[0040] Figure 6 The photocatalytic CO2 generation of the 20% BiOCl / TCN sample prepared in Example 1 changes with time;
[0041] Figure 7 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 1;
[0042] Figure 8 This is a photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 1;
[0043] Fig. 9 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 2;
[0044] Fig.10 This is a photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 2;
[0045] Fig.11 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 3;
[0046] Fig.12 This is a photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 3;
[0047] Fig.13 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 4;
[0048] Fig.14 This is the photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 4. DETAILED DESCRIPTION
[0049] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0050] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0051] Example 1
[0052] A method for preparing a hierarchical structure bismuth oxychloride / TCN composite material comprises the following steps:
[0053] (1) 1.0 g of melamine and 1.2 g of phosphoric acid were dissolved in 80 mL of deionized water and heated at 80° C. for 1 hour. Then, the obtained mixed solution was placed in a stainless steel autoclave and heated at 180° C. for 10 hours. The reaction product was fully rinsed with deionized water until the phosphorus species were removed. The obtained precursor was calcined in a tube furnace at 550° C. in a N2 atmosphere for 4 hours. After cooling, tubular carbon nitride was obtained, which was named TCN.
[0054] (2) The obtained TCN was immersed in a 2M NaOH solution for 10 hours to perform surface hydrophilic treatment, and then the hydrophilic TCN was washed with deionized water to neutrality. Subsequently, 50 mg of hydrophilic TCN and 0.25 mmol Bi(NO3)3·5H2O were dispersed in 5 mL of ethylene glycol under stirring to form solution A, 0.05 mmol [C16-MIm]Cl was dissolved in 30 mL of ethanol to obtain solution B, and solution B was dropped into solution A and stirred under magnetic stirring for 30 minutes. The obtained mixture was transferred to a 50 mL stainless steel autoclave, heated at 160°C for 10 hours, and naturally cooled to room temperature. Finally, the obtained precipitate was collected by centrifugation, thoroughly washed with ethanol and deionized water, and then dried at 60°C overnight to obtain a hierarchical structure bismuth oxychloride / TCN composite material, named 20% BiOCl / TCN.
[0055] 200 mL of tetracycline solution with a concentration of 20 mg / L was added to the photocatalytic reactor, followed by 50 mg of 20% BiOCl / TCN composite material, and ultrasonic treatment was performed for 30 minutes until it was completely dispersed. Next, high-purity CO2 was injected into the photocatalytic reactor until adsorption-desorption equilibrium was reached. A 300W xenon lamp and a 400nm cutoff filter were used as the light source, and the reaction temperature was maintained at about 25°C by circulating cooling water. During the entire photocatalytic process, 1 mL of gas was extracted every 1 hour, and qualitative and quantitative analysis was performed using a gas chromatograph equipped with TCD and FID detectors. At the same time, 1.5 mL of tetracycline solution was extracted from the lower port of the reactor, and the degradation products were analyzed using a UV-visible spectrophotometer. The following results were obtained for the entire reaction:
[0056] The product of CO2 photoreduction by 20% BiOCl / TCN is CH4, and the average generation rate of CH4 is 34.6 μmol g - 1 h -1 ; At the same time, the removal rate of tetracycline is 94.3%.
[0057] Example 2
[0058] Compared with Example 1, the only difference of Example 2 is that the amount of Bi(NO3)3·5H2O is halved, and the other processes are the same as those of Example 1. The obtained product is named 10%BiOCl / TCN.
[0059] Example 3
[0060] Compared with Example 1, the only difference of Example 3 is that the amount of Bi(NO3)3·5H2O is increased by 1.5 times, and the other processes are the same as those of Example 1. The obtained product is named 30%BiOCl / TCN.
[0061] Comparative Example 1
[0062] Compared with Example 1, the only difference of Comparative Example 1 is that in step (2), no NaOH solution is used to soak TCN, and the other processes are the same as those of Example 1.
[0063] The photocatalytic reaction was carried out under the same conditions as in Example 1. The catalytic result of the product prepared in Comparative Example 1 was that the average generation rate of CH4 was 15.4 μmol g -1 h -1 ; The removal rate of tetracycline is 49.4%.
[0064] Comparative Example 2
[0065] Compared with Example 1, the difference of Comparative Example 2 is that in step (2), an equal amount of NaCl is used to replace [C16-MIm]Cl, and the other processes are the same as those of Example 1.
[0066] The photocatalytic reaction was carried out under the same conditions as in Example 1. The catalytic result of the product prepared in Comparative Example 2 was that the average generation rate of CH4 was 12.8 μmol g -1 h -1 ; The removal rate of tetracycline is 43.2%.
[0067] Comparative Example 3
[0068] Compared with Example 1, the difference of Comparative Example 3 is that in step (2), an equal amount of 1-methyl-3-ethylimidazolium chloride ([emim]Cl) is used instead of [C16-MIm]Cl, and the other processes are the same as those of Example 1.
[0069] The photocatalytic reaction was carried out under the same conditions as in Example 1. The catalytic result of the product prepared in Comparative Example 3 was that the average generation rate of CH4 was 16.9 μmol g -1 h -1 ; The removal rate of tetracycline was 56.2%.
[0070] Comparative Example 4
[0071] Compared with Example 1, the only difference of Comparative Example 4 is that an equal amount of glycerol is used instead of ethylene glycol in step (2), and the other processes are the same as those of Example 1.
[0072] The photocatalytic reaction was carried out under the same conditions as in Example 1. The catalytic result of the product prepared in Comparative Example 4 was that the average generation rate of CH4 was 19.3 μmol g -1 h -1 ; The removal rate of tetracycline is 74.5%.
[0073] Comparative Example 5
[0074] The product BiOI(110) / g-C3N4 prepared in Example 1 of CN111437856A was subjected to photocatalytic reaction under the same conditions as in Example 1. After 60 minutes of reaction, the average generation rate of CH4 was 14.3 μmol g -1 h -1 ; The removal rate of tetracycline is 56.3%.
[0075] Figure 1 X-ray diffraction spectra of BiOCl, TCN and 20% BiOCl / TCN samples; Figure 1 The "2θ" in it represents the diffraction angle, the "degree" represents the degree, and the "Intensity" represents the intensity.
[0076] Figure 2 IR spectra of BiOCl, TCN and 20% BiOCl / TCN samples; Figure 2 “Wavenumber” means wave number, and “Transmittance” means transmittance.
[0077] Figure 3 Scanning electron microscope image and element distribution of 20% BiOCl / TCN sample.
[0078] Figure 4 The photocatalytic tetracycline degradation performance diagram of different samples; Figure 4 "Time" means time, "C t " / C0" represents the ratio of the concentration of tetracycline to the initial concentration of tetracycline after the sample has been photocatalytically degraded for a certain period of time, "Dark" represents darkness, i.e., no light, and "Light on" represents light. Among them, "20%BiOCl / TCN" corresponds to the sample prepared in Example 1, "10%BiOCl / TCN" corresponds to the sample prepared in Example 2, and "30%BiOCl / TCN" corresponds to the sample prepared in Example 3.
[0079] Figure 5 The photocatalytic CO2 reduction performance diagram of different samples; Figure 5 “Average CH4 production” represents the average generation rate of CH4, “20% BiOCl / TCN” corresponds to the sample prepared in Example 1, “10% BiOCl / TCN” corresponds to the sample prepared in Example 2, and “30% BiOCl / TCN” corresponds to the sample prepared in Example 3.
[0080] Figure 6 The relationship between the photocatalytic CO2 reduction performance and time of the 20% BiOCl / TCN sample prepared in Example 1; Figure 6Here, “CH4 production” refers to the amount of CH4 generated, and “Time” refers to the time.
[0081] Figure 7 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 1; "CH4 production" represents the amount of CH4 generated, and "Time" represents the time.
[0082] Figure 8 The photocatalytic tetracycline degradation performance of the sample prepared in Comparative Example 1 is shown in FIG. 1 ; “Time” indicates time, “C t " / C0" means the ratio of the concentration of tetracycline to the initial concentration of tetracycline after the sample has been photocatalytically degraded for a certain period of time, "Dark" means darkness, i.e. no light, and "Light on" means light.
[0083] Fig. 9 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 2; "CH4 production" represents the amount of CH4 generated, and "Time" represents the time.
[0084] Fig.10 The photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 2; "Time" represents time, "C t " / C0" means the ratio of the concentration of tetracycline to the initial concentration of tetracycline after the sample has been photocatalytically degraded for a certain period of time, "Dark" means darkness, i.e. no light, and "Light on" means light.
[0085] Fig.11 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 3; "CH4 production" represents the amount of CH4 generated, and "Time" represents the time.
[0086] Fig.12 The photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 3; "Time" represents time, "C t " / C0" means the ratio of the concentration of tetracycline to the initial concentration of tetracycline after the sample has been photocatalytically degraded for a certain period of time, "Dark" means darkness, i.e. no light, and "Light on" means light.
[0087] Fig.13 The relationship between the photocatalytic CO2 reduction performance and time of the sample prepared in Comparative Example 4; "CH4 production" represents the amount of CH4 generated, and "Time" represents the time.
[0088] Fig.14 This is a photocatalytic tetracycline degradation performance diagram of the sample prepared in Comparative Example 4. “Time” represents time, “Ct " / C0" means the ratio of the concentration of tetracycline to the initial concentration of tetracycline after the sample has been photocatalytically degraded for a certain period of time, "Dark" means darkness, i.e. no light, and "Light on" means light.
[0089] X-ray diffraction and infrared spectra show that BiOCl and TCN are effectively composited ( Figure 1 and Figure 2 ); SEM images and element distribution showed that BiOCl nanosheets grew on the surface of TCN, resulting in a hierarchical heterojunction ( Figure 3 ); The tetracycline degradation and CO2 reduction performance diagrams show that the 20% BiOCl / TCN prepared in Example 1 can effectively remove pollutants and convert CO2 ( Figure 4 , Figure 5 and Figure 6 ).
[0090] from Figures 4 to 6 and Figures 7 to 14 It can be seen that the hierarchical bismuth oxychloride / TCN composite material sample prepared in the embodiment of the present invention has better photocatalytic tetracycline degradation performance and better CO2 reduction performance.
[0091] The above content describes the basic principle and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that protection scope of the present invention is not limited by the above-described embodiments. Without departing from the spirit and scope of the present invention, the present invention also has various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed for protection.
Claims
1. A method for preparing a hierarchical structure bismuth oxychloride / TCN composite material, characterized in that: The following steps are involved: (1) mixing melamine with phosphoric acid and water, heating, and then further heating, reacting, washing the reaction product to obtain a precursor, and calcining under a protective gas atmosphere to obtain tubular carbon nitride; (2) soaking the tubular carbon nitride obtained in step (1) in an alkali solution, performing a surface hydrophilic treatment, and then washing to obtain the hydrophilic treated tubular carbon nitride, and then mixing the hydrophilic treated tubular carbon nitride, bismuth nitrate or bismuth nitrate hydrate, and ethylene glycol to obtain a solution A; dissolving 1-hexadecyl-3-methylimidazolium chloride in ethanol to obtain a solution B, dripping the solution B into the solution A, stirring, heating the obtained mixture for reaction, and finally collecting the obtained precipitate by centrifugation, washing, and drying to obtain the hierarchical structure bismuth oxychloride / TCN composite material.
2. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (1), the mass volume ratio of melamine, phosphoric acid and water is 1 g: (0.5-2.0) g: (80-100) mL.
3. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (1), the heating temperature is 75-85° C. and the heating time is 0.5-1.5 hours.
4. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (1), the reaction temperature is 170-180° C. and the reaction time is 8-10 hours.
5. The method for preparing the hierarchical structure bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (1), the calcination temperature is 500-550° C. and the calcination time is 3-4 hours.
6. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (2), the usage ratio of the hydrophilic treated tubular carbon nitride, bismuth nitrate or bismuth nitrate hydrate, and ethylene glycol is 50 mg: (0.1-0.25) mmol: (5-10) mL.
7. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (2), the ratio of 1-hexadecyl-3-methylimidazolium chloride to ethanol is (0.01-0.05) mmol: (20-30) mL.
8. The method for preparing the hierarchical bismuth oxychloride / TCN composite material according to claim 1, characterized in that: In step (2), the heating reaction temperature is 150-160° C., and the heating reaction time is 8-10 hours.
9. A hierarchical structure bismuth oxychloride / TCN composite material, characterized in that: The hierarchical bismuth oxychloride / TCN composite material is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the hierarchical bismuth oxychloride / TCN composite material according to claim 9 in catalyzing the decomposition of antibiotics.
Citation Information
Patent Citations
Preparation of bismuth oxyhalide / g-C3N4 heterojunction photocatalyst
CN111437856A
Nitrated carbon fiber loaded bismuth oxyhalide nanoflower and preparation method of nanoflower
CN103920508A
Phosphorus-doped tubular carbon nitride micro-nano material and application thereof in waste gas catalytic treatment
CN109772418A
Nano bismuth oxychloride / carbon nitride composite material, preparation method and application thereof
CN111330615A
Composite visible-light-induced photocatalyst and preparation method thereof
CN112742437A